To be or not to be a valid genus: the systematic position of Ophyra R.‐D. revised (Diptera: Muscidae). (19th May 2017) - GRZYWACZ, ANDRZEJ; WALLMAN, JAMES F.; PIWCZYŃSKI, MARCIN
Abstract: Ophyra Robineau‐Desvoidy is one of the better‐studied genera of the family Muscidae (Diptera). The larvae of species of this genus feed on highly decomposed organic matter of various origins, and may reveal predatory behaviour as they mature. These feeding habits, combined with the widespread distribution and close association with human dwellings of some species, give the genus commercial and medico‐legal importance. However, the systematic position of Ophyra has been a matter of debate for many years. Ophyra has been considered by muscid workers to be either a valid genus or a junior synonym of Hydrotaea Robineau‐Desvoidy. A lack of agreement about the systematic position of Ophyra has led to serious errors, particularly in the applied literature. Recent molecular and morphological studies provided contradictory information on the validity of the genus and its subfamilial classification. We revise the systematic position of Ophyra herein by means of molecular phylogenetic reconstruction. Our results are incongruent with opinions on the systematic position of Ophyra based on previously published molecular phylogenies, although they correspond with the concept of the genus based on adult morphology. All analyses of the concatenated dataset revealed Ophyra as monophyletic and placed within a paraphyletic Azeliini. Depending on the phylogenetic approach, Ophyra was placed within either a monophyletic, paraphyletic or polyphyletic Hydrotaea, yet always closely related to a certain group of species. We conclude that Ophyra, as currently defined, should not be considered a valid name, yet a detailed reconstruction of the genus Hydrotaea awaits future studies with greater increases in both taxon sampling and the number of molecular markers. Abstract : The systematic position of Ophyra revised by means of molecular phylogenetic reconstruction. Ophyra placed within Hydrotaea and always closely related to a certain group of species. Results are incongruent with previous molecular phylogenies. Ophyra, as currently defined, should not be considered a valid name.